Pharmacist-driven antimicrobial stewardship interventions in patients with COVID-19: a scoping review - Z. G. Nasr (17785694) (2023)
Background Coronavirus Disease 2019 (COVID-19) is a highly infectious disease that can be treated with antivirals in addition to other antimicrobials in cases of secondary or concomitant infections. This creates potential for antimicrobials misuse, which increases antimicrobial resistance (AMR). Pharmacists are known to undertake prominent roles in combatting AMR. Aim The aim of this review was to characterize pharmacist-driven interventions that have been performed in patients with COVID-19 globally and describe their impact on antimicrobial use. Method We followed the Joanna Briggs Institutes manual framework for scoping reviews in our study. Studies that reported antimicrobial stewardship (AMS) interventions performed by pharmacists in COVID-19 patients were included. Articles that did not report outcomes or did not mention pharmacists in the intervention were excluded. Restrictions included English-only articles from inception date until June 2022. Articles were searched from four databases. Results Eleven publications were included in the review. The most common AMS intervention was pharmacist-driven interventions reported in 63.2% of all studies, followed by guideline development and application (26.3%), and medication supply coordination (10.5%), respectively. The outcomes of the interventions were difficult to compare but showed a reduction in antimicrobial use and prevention of adverse drug reactions with a relatively high acceptance rate from physicians. Conclusion Pharmacists played an important role in performing AMS-related interventions in COVID-19 patients and helped in the fight against the worsening of AMR during the pandemic. The impact of pharmacist-driven AMS interventions in patients with COVID-19 seemed to be positive and improved outcomes related to antimicrobial use. Other Information Published in: International Journal of Clinical Pharmacy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11096-023-01574-0